The effect of physical activity on lymphocyte count in smokers who consume black cumin seed (Nigella sativa L.) oil - Titiek Hidayati; Akrom Akrom; Laili Apriani (Intelektual Pustaka Media Utama, 2020)
Twenty percent of the total number of human leukocytes is lymphocytes. Lymphocytes are responsible for the control of the adaptive immune system. Physical activity is any body movement that requires energy to do it. Physical activity is related to changes in a person's immunity so that it can reduce the risks of diseases such as obesity, hypertension, diabetes, cancer, and stroke. Black Cumin Seed Oil (BCSO) in various studies has been widely used as a supplement, especially as an immune-modulator. The purpose of this study is to see the effect of physical activity on lymphocyte levels in smokers who have been given Black Cumin Seed Oil for 30 days. This study used a single-blind Randomized Controlled Trial (RCT) method, with a total of 36 test subjects divided into four groups. Group 1 received placebo 3x1 capsules/day, group 2 received BCSO 3x1 capsules/day, group 3 received BCSO 3x2 capsules/day, and group 4 received BCSO 3x3 capsules/day. The intervention was carried out for 30 days, then on the 31st-day blood was drawn for analysis. Data analysis using an independent t-test to see the average group with high and low activity, while to see the average lymphocyte between treatment groups using one way ANOVA test. The test results were said to be significant if p <0.05. The p-value of the independent t-test is 0.045, and one way ANOVA test p-value is 0.343. In conclusion, physical activity can increase lymphocyte levels significantly, but not on BCSO administration.